Cleavage Stimulation Factor Subunit 2: Function Across Cancers and Potential Target for Chemotherapeutic Drugs - Linfei Feng; Fengyang Jing; Xiaofeng Qin; Liming Zhou; Yujie Ning; Jun Hou; Weihao Kong; Youming Zhu (Frontiers Media S.A., 2022)
The cleavage stimulation factor subunit complex is involved in the cleavage and polyadenylation of 3'-end pre-mRNAs that regulate mRNA formation and processing. However, cleavage stimulation factor subunit 2 (CSTF2) was found to play a more critical regulatory role across cancers. General cancer data sets from The Cancer Genome Atlas and Genotype-Tissue Expression project were thus downloaded for differential analysis, and the possible functions and mechanisms of CSTF2 in general cancer were analyzed using the Compartments database, cBioPortal database, Tumor Immune Single-cell Hub database, and Comparative Toxigenomics database using gene set enrichment analysis and R software. The results showed that CSTF2 could affect DNA repair and methylation in tumor cells. In addition, CSTF2 was associated with multiple tumor immune infiltrates in a wide range of cancers, and its high expression was associated with multiple immune checkpoints; therefore, it could serve as a potential target for many drug molecules. We also proved that CSTF2 promotes oral cell proliferation and migration. The high diagnostic efficacy of CSTF2 suggested that this gene may act as a new biomarker and personalized therapeutic target for a variety of tumors.